Legalization of Informal Hibah and Wasiat through Isbat Hibah and Wasiat in Religious Courts - Hidayat, Rahmat; Aseri, Akh Fauzi; Hanafiah, M (Fakultas Syariah UINSI Samarinda, 2023)
Abstract Based on the Religious Judiciary Annual Report in 2020, there have been many lawsuits for hibah and wasiat in the religious courts due to informal hibah and wasiat. On the other hand, there are no rules governing the religious courts' authority in legalizing the practice of informal hibah and wasiat. This study initiated the discourse on the legalization of informal hibah and wasiat through isbat hibah and wasiat in the religious courts. Hence, what are isbat hibah and wasiat and their legal basis as a renewal of the religious courts' authority in Indonesia? This study is normative legal research in which legal norms in statutory regulations are examined as research objects. This study's results indicate that informal hibah and wasiat still occur in society, which raises social problems such as conflicts between recipients of informal hibah and wasiat and the heirs of informal hibah and wasiat. These social problems occur when the giver or recipient of informal hibah or wasiat passes away. Meanwhile, the subject or object of the related hibah and wasiat does not yet have a formal foundation. Legal problems related to informal hibah and wasiat lead to legality issues due to the absence of authentic evidence showing that the subject or related object has given or received a certain hibah or wasiat. Even though every legal action must be carried out legally and formally, The concept of isbat hibah and wasiat under the authority of religious courts aims to achieve the certainty, fairness, and legal benefits of informal hibah and wasiat. Keywords: Legalization, informal hibah and wasiat, isbat, Indonesia Religious Courts.